Mechanistic links between coexistence, productivity, and stability in experimental grasslands - Pubin Hong; Bernhard Schmid; Dylan Craven; Maowei Liang; Mingyu Luo; Zeyu Wang; Chen Yang; Libin Zhou; Eric Allan; Jane A. Catford; Nico Eisenhauer; Yanhao Feng; et al. (Proceedings of the National Academy of Sciences, 2026)
The escalating biodiversity crisis underscores the urgent need for a unified framework that links the mechanisms maintaining biodiversity to its functional consequences. However, studies of species coexistence and biodiversity effects on ecosystem functioning have largely progressed independently. Here, using long-term data from five grassland biodiversity experiments, we quantified “coexistence potential” (i.e., the degree to which niche differences exceed fitness differences) and tested its relationships with biodiversity effects on both ecosystem productivity (via complementarity and selection effects) and stability (via species asynchrony and species stability). We found that the relationships within the coexistence–productivity–stability triad were overall positive. These patterns were mechanistically explained by phylogenetic and trait composition: Phylogenetically and functionally more diverse communities supported higher coexistence potential and greater productivity, while those dominated by species with stronger root-mycorrhizal collaboration and larger seeds exhibited enhanced productivity and stability. Our work provides integrative empirical evidence linking biodiversity maintenance to ecosystem functioning, demonstrating that conserving phylogenetically and functionally diverse communities, particularly those including collaborative species, is key to sustaining biodiverse, productive, and stable ecosystems.